Lower Extremity Peripheral Artery Disease: Contemporary Epidemiology, Management Gaps, and Future Directions. Issue 9 (31st August 2021) - Criqui, Michael H.; Matsushita, Kunihiro; Aboyans, Victor; Hess, Connie N.; Hicks, Caitlin W.; Kwan, Tak W.; McDermott, Mary M.; Misra, Sanjay; Ujueta, Francisco
Abstract : Lower extremity peripheral artery disease (PAD) affects >230 million adults worldwide and is associated with increased risk of various adverse clinical outcomes (other cardiovascular diseases such as coronary heart disease and stroke and leg outcomes such as amputation). Despite its prevalence and clinical importance, PAD has been historically underappreciated by health care professionals and patients. This underappreciation seems multifactorial (eg, limited availability of the first-line diagnostic test, the ankle-brachial index, in clinics; incorrect perceptions that a leg vascular disease is not fatal and that the diagnosis of PAD would not necessarily change clinical practice). In the past several years, a body of evidence has indicated that these perceptions are incorrect. Several studies have consistently demonstrated that many patients with PAD are not receiving evidence-based therapies. Thus, this scientific statement provides an update for health care professionals regarding contemporary epidemiology (eg, prevalence, temporal trends, risk factors, and complications) of PAD, the present status of diagnosis (physiological tests and imaging modalities), and the major gaps in the management of PAD (eg, medications, exercise therapy, and revascularization). The statement also lists key gaps in research, clinical practice, and implementation related to PAD. Orchestrated efforts among different parties (eg, health care providers, researchers, expert organizations, and health care organizations) will be needed to increase the awareness and understanding of PAD and improve the diagnostic approaches, management, and prognosis of PAD.